2-Dimensional in vitro culture assessment of ovarian cancer cell line using cost effective silver nanoparticles from Macrotyloma uniflorum seed extracts - Lavudi, Kousalya; Harika, Venkata Satya; Kokkanti, Rekha Rani; Patchigolla, Swaroopa; Sinha, Anupriya; Patnaik, Srinivas; Penchalaneni, Josthna (Frontiers in Bioengineering and Biotechnology, 2022)
Our research focused on generating AgNPs using Macrotyloma uniflorum (MU) seed extracts and studied their efficacy in combating tumor growth using the 2-Dimensional method for ovarian cancer cell line-PA-1. Characterization studies including UV-Visible spectrophotometer confirmed the SPR peak of 436nm. Particle size determination data validated the nanoparticle diameter of 91.8nm. Synthesized AgNPs possess a negative charge of -28.0mV, which was confirmed through the zeta potential study. Structural characterization through XRD determined the crystal phase of AgNPs at 4 distant peaks at 2θ (38.17, 44.36, 64.52, and 77.46) and were assigned to 111,200,220 and 311 planes of FCC structure. FTIR studies have confirmed the presence of O-H, N-H, C=O, ethers, C-Br, and C-I groups in AgNPs respectively. Radical scavenging capacity has been confirmed via DPPH assay. MTT assay shows the efficacy of MU-AgNPs in reducing cell viability in cancer cells over control cell lines. ROS production affirms the capacity to induce DNA damage via apoptosis. Standard drug camptothecin generated 26% of ROS production which confirms the higher potential of AgNPs in inducing DNA damage in tumor cells without causing lethality to the healthy cells. Further, the FACS study using Caspase-3 confirms the generation of apoptotic bodies using MU-AgNPs. Propidium iodide-based Cell cycle study has shown a significant decrease in G0/G1 phase of cell cycle with respect to control confirmed the apoptotic induction. MMP studies using JC-1 dye, showed a significant increase in green fluorescence owing to lowered membrane potential, thus ensuring the breakdown of mitochondrial potential compared to untreated and standard drugs. With the obtained results, we are concluding that MU-AgNPs has a tremendous capacity to suppress ovarian cancer cell proliferation in vitro by inducing DNA damage and apoptosis.